2021
DOI: 10.1186/s13041-021-00779-6
|View full text |Cite
|
Sign up to set email alerts
|

Lack of the peroxiredoxin 6 gene causes impaired spatial memory and abnormal synaptic plasticity

Abstract: Peroxiredoxin 6 (PRDX6) is expressed dominantly in the astrocytes and exerts either neuroprotective or neurotoxic effects in the brain. Although PRDX6 can modulate several signaling cascades involving cognitive functions, its physiological role in spatial memory has not been investigated yet. This study aims to explore the function of the Prdx6 gene in spatial memory formation and synaptic plasticity. We first tested Prdx6−/− mice on a Morris water maze task and found that their memory performance was defectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…The procedure for the MWM test was conducted according to that used in our previous publication [ 8 ]. A circular pool (diameter 110 cm) was filled with water at room temperature (21 °C ± 1 °C).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The procedure for the MWM test was conducted according to that used in our previous publication [ 8 ]. A circular pool (diameter 110 cm) was filled with water at room temperature (21 °C ± 1 °C).…”
Section: Methodsmentioning
confidence: 99%
“…Then the hippocampal slices were transferred to a recording chamber for extracellular LTP recording. The recording procedure was conducted as described in our previous publication [ 8 ] . Slices were perfused with ACSF at a speed of 20 rpm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PRDX6 is involved in various forms of stress-related disorders [ 21 , 27 , 28 ]. Our previous studies have identified the PRDX6 function in modulating hippocampal synaptic plasticity and memory formation [ 29 , 30 ]. Thus, it is worth investigating whether PRDX6 is involved in stress-related anxiety response and memory performance.…”
Section: Introductionmentioning
confidence: 99%